EDUKASI PEMUDA PUTUS SEKOLAH DI DESA PANNYANGKALANG MELALUI BUDIDAYA MAGGOT DENGAN PEMANFAATAN SAMPAH ORGANIK - Wahda; Nurqamar, Insany Fitri; Sugiharti, Shinta Dewi Tikson; Muhammad Rifai; Fatmawati; Sri Ulfa (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
The accumulation of organic waste generated by community activities poses a risk of environmental pollution if not managed properly. In addition to causing unpleasant odors, unmanaged organic waste can become a breeding ground for disease vectors and may contaminate soil and water resources. One promising solution is the use of black soldier fly (Hermetia illucens) maggot cultivation, which converts organic waste into larval biomass used as feed. This approach not only reduces waste volume but also creates economic opportunities for local communities. Black soldier fly larvae have a short life cycle and a high capacity to decompose organic waste, making them a sustainable alternative for organic waste management. This program aimed to improve the literacy and competencies of out-of-school youth in Pannyangkalang Village regarding maggot cultivation techniques as a strategy to support local economic improvement. The implementation stages included obtaining permits, conducting site surveys, delivering initial outreach, and providing technical training on cage construction, colony maintenance, larval transfer, and harvesting procedures. Beyond its waste management function, maggot production has high economic value as livestock and fish feed and may serve as an additional source of income. Program evaluation indicated positive outcomes across several indicators: participants’ understanding and practical skills increased by 85%, 75% of participants adopted maggot cultivation practices, and organic waste accumulation decreased by 80%. Although improvements in income were not yet optimal, the program delivered tangible benefits to the community and demonstrated the potential of maggot cultivation as an empowerment strategy for out-of-school youth in Pannyangkalang Village. --- Timbunan limbah organik dari aktivitas masyarakat berisiko mencemari lingkungan apabila penanganannya tidak tepat. Selain menimbulkan aroma tidak sedap, akumulasi sampah organik dapat menjadi sarang penyakit serta mencemari tanah dan air. Solusi efektif yang ditawarkan adalah teknologi budidaya maggot (Hermetia illucens) dengan memanfaatkan limbah organik sebagai media pakan. Pendekatan ini tidak hanya mengurangi volume sampah, tetapi juga membuka peluang ekonomi. Maggot memiliki siklus hidup cepat dan kapasitas penguraian limbah organik yang tinggi, sehingga menjadi alternatif pengelolaan sampah yang berkelanjutan. Program ini dirancang untuk meningkatkan literasi dan kompetensi pemuda di luar sekolah di Desa Pannyangkalang dalam teknik budidaya maggot, sebagai upaya peningkatan taraf ekonomi. Tahapan pelaksanaan meliputi perizinan, survei lokasi, penyuluhan awal, serta pelatihan teknis yang mencakup konstruksi kandang, pemeliharaan bibit, transfer larva, dan teknik panen. Di sampung fungsi pengelolaan limbah, maggot bernilai ekonomis tinggi sebagai bahan pakan ternak dan ikan, sehingga berpotensi menjadi sumber pendapatan tambahan. Evaluasi program menunjukkan capaian positif pada sejumlah indikator, yaitu peningkatan pemahaman dan keterampilan peserta sebesar 85%, adopsi budidaya oleh 75% peserta, serta penurunan timbunan sampah organik mencapai 80%. Walaupun peningkatan pendapatan belum optimal, program ini berkontribusi nyata bagi masyarakat Desa Pannyangkalang dan membuktikan potensi budidaya maggot sebagai sarana pemberdayaan pemuda putus sekolah di Desa Pannyangkalang.